Routing in Delay Tolerant Mobile Network: A Comparative Analysis (International Journal of Engineering and Computer Science, 2014)
Routing in Delay Tolerant Network has received considerable attention in the recent years. Context-aware Adaptive routing and Reputation based Context-aware Adaptive routing are based on a single copy of the message, whose delivery is based on the choice of a best carrier node. In this paper, we present a comparative analysis of these algorithms and highlight the issues not addressed by any of these algorithm.